2010
DOI: 10.1007/s10815-010-9452-1
|View full text |Cite
|
Sign up to set email alerts
|

Human cleavage-stage embryo vitrification is comparable to slow-rate cryopreservation in cycles of assisted reproduction

Abstract: These data suggest that vitrification of human embryos during assisted reproduction cycles achieves comparable success rates to fresh cycles and therefore can be applied in the laboratory of assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…In the current study, we found that slow [9] and may have higher potential cell toxicity, which may be one of the major factors affecting development of embryos. Several studies have shown similar pregnancy and implantation rates between slow freezing and vitrification [13,27]. Vitrified embryo transfer is associated with lower hCG concentrations on day 12 post-embryo transfer compared with slow freezing embryo transfer [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we found that slow [9] and may have higher potential cell toxicity, which may be one of the major factors affecting development of embryos. Several studies have shown similar pregnancy and implantation rates between slow freezing and vitrification [13,27]. Vitrified embryo transfer is associated with lower hCG concentrations on day 12 post-embryo transfer compared with slow freezing embryo transfer [18].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to switch the cryopreservation protocol was based on the reported high embryo survival rate, low risk of losing the chance of embryo transfer [10,11], and higher blastulation rates [12] by vitrification. However, some previous studies have found no difference in the pregnancy rate between vitrification and slow freezing [13,14]. Therefore, there is an obvious need to analyze the results of two cryopreservation protocols before totally abandoning slow freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Technically, the method is able to decrease damaged embryo cells due to freezing. In addition, vitrification method is able to reduce damaged embryos due to freezing as critical temperature can be exceeded quickly (Wilding et al, 2010;Turathum et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, excess embryos are available for cryopreservation. Cryopreservation of surplus embryos increases the chances of conception, improves the cumulative pregnancy rates (AbdelHafez et al, 2010;Liebermann, 2009) and reduces cost of treatment (Wilding et al, 2010;Vajta and Nagy, 2006. Another benefit of cryopreservation is minimization of adverse effects of repeated ovarian stimulation (AbdelHafez et al, 2010;Shamonki and Oktay, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different cryopreservation methods known, vitrification leads to higher survival rate of embryos (Wilding et al, 2010) because it prevents the formation of ice crystals inside and outside the cells (Rama Raju et al, 2005). The main disadvantage of this method is exposure of embryos to high concentrations of cryoprotectants in the vitrification solution, which may have a detrimental effect on them (Rezazadeh Valojerdi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%